Metode Monte Carlo untuk Memprediksi Jumlah Tamu Menginap - Hasnatul Hidayah (Jurnal Informasi dan Teknologi, 2022)
The Mandeh Tourism Area is one of the most visited marine tourism destinations in West Sumatra. The Mandeh Tourism Area is also included in one of the tourism and creative economy development programs by the Government of the Republic of Indonesia. Baga Beach Cottage is one of the inns located in the Mandeh Tourism Area. Currently the inn consists of 5 cottages that can accommodate 30 guests. At certain times this inn cannot accommodate all the guests who want to stay, so it is recommended to go to another inn, this of course reduces the amount of income that should be obtained. Therefore, I want to predict the number of guests using the Monte Carlo method which is expected to be used to make it easier for business managers to make decisions. This study aims to predict the number of guests staying in the following year which is expected to be used to facilitate business managers in making decisions. The data processed is data on the number of guests staying from 2018 to 2020 using the Monte Carlo method. The results of data processing show that the level of prediction accuracy using the Monte Carlo method is 84%. The Monte Carlo method can be used to predict the number of guests staying at Baga Beach Cottage in the following year so that it can be used to facilitate business managers in making decisions.